Удмуртские народные сказки - Кралина Надежда Петровна (Удмуртия, 2016)
Экземпляры: (20170620) / Инвентарный номер: 49665 / Цена: 316.00 / Сис.шифр: 82.3(2Рос=Удм) / Авт.знак: У 30 / ГРНТИ: 17.71 / ББК: 82.3(2Рос=Удм)